Effects of addition of BT on structural phase formation and electrical properties of relaxor ferroelectric Pb(In0.5Nb0.5)(1-x)Ti(x)O3ceramics - S. Wongsaenmai (2018)
In this study, the solid solution of Pb(In0.5Nb0.5)(1-x)Ti(x)O3with 20 mol% of BT (where x = 0.0, 0.1, 0.2 and 0.3) ceramics was prepared by the wolframite precursor method via a vibro-milling technique. The concentration of 20 mol% of BT was the lowest amount of BT to help stabilize the perovskite phase formation of PIN ceramics in this study. The variation of x between 0.0 and 0.3 (0.0 ≤ x ≤ 0.3; Δx = 0.1) was chosen based on the non-MPB composition of this PINT system to focus on the compositions with relaxor behavior. The phase formation of the ceramics was investigated as a function of compositions. The XRD patterns investigation showed that the ceramics gradually changed from the pseudo-cubic to tetragonal phase between the compositions x = 0.2 and 0.3, indicating a shift in the MPB of the PINT system with BT addition. Correspondingly, large dielectric constant maximum (εm) was observed over the same compositions. The remanent polarization (Pr) was also maximized at this composition, which indicated enhanced electrical properties near the MPB of this PBINT system. These results clearly indicated that the addition of BT had strong influence on phase formation and the electrical properties of the PINT system. © 2008 Elsevier B.V. All rights reserved.